Analisis Kadar Flavonoid pada Batang Jarak Pagar (Jatropha curcas L.), Jarak Merah (Jatropha gossypifolia L.), dan Jarak Kepyar (Ricinus communis L.) - Kesumasari, Ni Made; Napitupulu, Mery; Jura, Minarni Rama (Jurnal Akademika Kimia, 2018)
This study aimed to determine flavonoids levels contained in each of jatropha plant samples to be used as an alternative affordable free radicals deterrent. The flavonoid content was analyzed using UV-Vis spectrophotometry. Stem of the three samples was extracted using HCl. The results showed that total flavonoids levels contained in each stem of Jatropha curcas L., Jatropha gossypifolia L., and Ricinus communis L. were 3.959 mg/L, 1.309 mg/L, and 0.083 mg/L, respectively.